Fraud Management of Social Assistance Prior to and During the Execution of Regional Head Election on Some Districts and Cities in North Sulawesi Indonesia - Saerang, Ivone S.; Karamoy, Herman; Lengkong, Victor P. K. (International Journal of Economics and Financial Issues, 2018)
This study aims to find out whether government officials understand the mechanism of social assistance and grants and its legal basis for execution to minimize fraud prior to and during the execution of regional head election in South Minahasa district and Tomohon city. In addition, it aims to find out the mechanism of planning and budgeting, the process and the form, as well as the objective of social assistance and grants. Data collection techniques and procedures through in-depth interview to a number of key informants related to local financial management especially social assistance in the context of prior to and during the execution of the election. The key informants include head of planning and budgeting division, head of treasury division, and head of assets division in South Minahasa district and Tomohon city. The result of research concludes that the understanding of government officials regarding to the mechanism of social assistance and grants and to avoid misdirection and unsuitable provision of social assistance and grants, which in turn can be a finding of Audit Board of the Republic of Indonesia due to fraud. Government officials in South Minahasa district and Tomohon city distribute social assistance and grants in accordance with Minister of of Internal Affairs Regulation Number 14 0f 2016 as a substitute for Regulation Number 32 of 2011. In addition, there are regulations of head of regional in each region. Other basis consideration in social assistance and grants based on the instruction of the Ministry of Internal Affairs and Audit Board of the Republic of Indonesia, and Ministry of Finance. Most regions implement the mechanism of social assistance and grants according to the prevailing laws. The form of grants according to law and regulation is in the form of services, goods, and money. The purpose of social assistance and grants is to minimize social risks such as social crisis, economic crisis, political crisis, phenomenon and natural disaster. Social assistance is target to the poor and grant is to support the achievement or target of local government. Keywords: social assistance, grants, fraud JEL Classifications: D73, H81